The Challenges of Nursing Students in the Clinical Learning Environment: A Qualitative Study - Nahid Jamshidi; Zahra Molazem; Farkhondeh Sharif; Camellia Torabizadeh; Majid Najafi Kalyani (The Scientific World Journal)
Background/Aim. Clinical learning is a main part of nursing education. Students’ exposure to clinical learning environment is one of the most important factors affecting the teaching-learning process in clinical settings. Identifying challenges of nursing students in the clinical learning environment could improve training and enhance the quality of its planning and promotion of the students. We aimed to explore Iranian nursing students’ challenges in the clinical learning environment. Materials and Methods. This is a qualitative study using the content analysis approach. The participants consisted of seventeen nursing students and three nursing instructors. The participants were selected through purposive sampling method and attended semistructured interviews and focus groups. Results. Three themes emerged after data analysis, including ineffective communications, inadequate readiness, and emotional reactions. Conclusion. Nursing students in Iran are faced with many challenges in the clinical learning environment. All challenges identified in this study affected the students’ learning in clinical setting. Therefore, we recommend that the instructors prepare students with a specific focus on their communication and psychological needs.